Neutrophil extracellular traps and echogenicity of carotid atherosclerotic plaques - I. I. Dolgushin; V. V. Genkel; A. Y. Savochkina; I. V. Samuseva; I. L. Baturina; M. A. Zotova; I. V. Emelyanov; A. S. Kuznetsova (Фундаментальная и клиническая медицина)
Aim. To study the association between the number of neutrophil extracellular traps (NETs) formed by circulating neutrophils and echogenicity of carotid atherosclerotic plaques. Materials and Methods. We enrolled 72 patients (40-64 years of age) without the clinical signs of atherosclerotic vascular disease, who then underwent ultrasound duplex scanning of carotid arteries. Grayscale median analysis of the images was performed using Adobe Photoshop CS6 software. Neutrophils were stained and examined by means of light microscopy to count NETs. Results. Carotid atherosclerotic plaques were found in 69.4% of asymptomatic patients. Echogenicity of atherosclerotic plaques inversely correlated with the number of NETs (r = - 0.310; p = 0.029). The number of NETs in patients with echolucent plaques (GSM < 60) was significantly higher in comparison with echogenic plaques (GSM ≥ 60, p = 0.042).